(untitled) (Revista Electrónica Calidad en la Educación Superior, 2025)
During the pandemic provoked by COVID-19, the Movingonline initiative provided urgent support to students, teachers, and education managers in Latin America and the Caribbean as they transitioned to online learning. This essay analyzes key lessons from the experience, and its contributions to digital transformation, teaching competencies development, and hybrid education. It highlights shifts in understanding professional development needs and effective formats and content for ongoing training. The reflection emphasizes the importance of flexibility, socioemotional support, and peer collaboration, and underscores the complementary role of online education. The conclusions offer recommendations to sustainably strengthen teacher and leadership development beyond crisis response